Anti-Angiogenesis Maintenance Therapy in Newly Diagnosed and Relapsed Ovarian Cancer: A Meta-analysis of Phase III Randomized Controlled Trials - Yizi Wang; Shitai Zhang; Zixuan Song; Ling Ouyang; Yan Li (Frontiers Media S.A., 2021)
Aim: Anti-angiogenesis agents have been added as maintenance therapy in ovarian cancer over the past decade. The aim of this meta-analysis was to analyze the efficacy of anti-angiogenesis therapy in newly diagnosed and relapsed ovarian cancer.Methods: PubMed, Embase, and Cochrane databases were searched for all phase III randomized controlled trials (RCTs) that assessed the efficacy and toxicity of anti-angiogenesis agents in ovarian cancer. Overall survival (OS) and progression-free survival (PFS) were used to evaluate the effectiveness of anti-angiogenesis therapy in ovarian cancer.Results: A total of 6097 patients with newly diagnosed ovarian cancer from 5 phase III RCTs and 2943 patients with relapsed ovarian cancer from 6 phase III RCTs were included in this meta-analysis. The pooled results showed that anti-angiogenesis maintenance therapy significantly improved PFS (hazard ratio [HR], 0.84; 95% confidence interval [CI], 0.76-0.93; p = 0.001), but not OS (HR, 0.98; 95% CI, 0.91-1.05; p = 0.49) compared with placebo in patients with newly diagnosed ovarian cancer. In patients with relapsed ovarian cancer, the pooled results showed a significant improvement on OS (HR, 0.89; 95% CI, 0.82-0.98; p = 0.02) and PFS (HR, 0.61; 95% CI, 0.52-0.72; p < 0.001). The pooled results also showed that the anti-angiogenesis agents were associated with an increase in the occurrence of severe hypertension, neutropenia, diarrhea, thrombocytopenia, headache, and bleeding in ovarian cancer. However, infrequent fatal adverse events occurred in the anti-angiogenesis groups.Conclusions: Study results suggest that anti-angiogenesis agents were an effective therapy for newly diagnosed and relapsed ovarian cancer, especially for relapsed ovarian cancer. Anti-angiogenesis agents may be associated with some severe but not fatal adverse events.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier CRD42021283647